HUBUNGAN SIKAP MERAWAT LUKA DENGAN PERCEPATAN FASE INFLAMASI LUKA PERINEUM IBU NIFAS DI RUMAH SAKIT BHAYANGKARA MAKASSAR - julianus ake (Stikes Graha Edukasi Makassar, 2020)
Objective: to know correlation attitude of wound care with acceleration phase inflammation of perineal wound in RS Bhayangkara Makassar. Method: The research design used was Cross Sectional. The population in this study were all postpartum mothers with perineal lesions at Bhayangkara Hospital Makassar with a sample of 48 people. Result: The result of the research obtained from 48 respondents got the respondents who have good knowledge as many as 44 people (91,7%), and that have less good knowledge as much as 4 people (8,3%), As for acceleration of inflamasi phase got respondent experiencing rapid inflammatory phase of 39 people (81.2%) and respondents who experienced a slow inflammation phase of 9 people (18.8%). Discussion: Perineal wound care to prevent infection in the vulva, perineum or inside the uterus, maintains perineal and vulvar hygiene and for perineal stitch wound healing due to the average dry and good seams wound in less than a week. Conclusion: In this study the conclusion is that there is a correlation between the attitude of treating the wound with the accelerated phase of perineal wound inflammation